N-f sentence example

n-f
  • di g d tan i g dt - v cos i ' and now (53) dx d 2 y dy d2xdx Cif dt 2 dt dt2 _ - _ gdt' and this, in conjunction with (46) dy _ d y tan i = dx dt/dt' (47)di d 2 d d 2 x dx sec 2 idt = (ctt d t - at dt2) I (dt), reduces to (48) Integrating from any initial pseudo-velocity U, (60) du t _ C U uf(u) x= C cos n f u (u) y=C sin n ff (a); and supposing the inclination i to change from 0, to 8 radians over the arc.
    0
    0
  • Now taking equation (72), and replacing tan B, as a variable final tangent of an angle, by tan i or dyldx, (75) tan 4) - dam= C sec n [I(U) - I(u)], and integrating with respect to x over the arc considered, (76) x tan 4, - y = C sec n (U) - f :I(u)dx] 0 But f (u)dx= f 1(u) du = C cos n f x I (u) u du g f() =C cos n [A(U) - A(u)] in Siacci's notation; so that the altitude-function A must be calculated by summation from the finite difference AA, where (78) AA = I (u) 9 = I (u) or else by an integration when it is legitimate to assume that f(v) =v m lk in an interval of velocity in which m may be supposed constant.
    0
    0
  • b n f?
    0
    0
  • V = 3rA = 2 1 4 / 3 n F tan -II cot e a = 2 I 1 3 n F cot e a cos a/ (sin' a -cos t 13) 2 R =1-/ tan IT tan 0=1/ sin 13/(sin e a-cost r =Zl tan 21 cot a= Il cot a cos 13/(sin" a -cos' (3)L 1 In the language of Proclus, the commentator: " The equilateral triangle is the proximate cause of the three elements, ` fire,' ` air ' and ` water '; but the square is annexed to the ` earth.'
    0
    0
  • N was i n f a v o u r o u r of inviting him.
    0
    0
    Advertisement
  • N was i n f a v o u r of inviting him.
    0
    0
  • N NAF The UKâs market leader in natural equine feed supplements.
    0
    0
  • (63) 0-0 =Cg cos n f u Au), 6 (4) tan 4 - tan g =Cg sec ?if u f(u)' But according to the definition of the functions T, S, I and D of the ballistic table, employed for direct fire, with u written for v, (65) ('u du _ du T(U) - T(u), J uf(??) - f g (66) ru du J f(u) (67) g du f uf(u) and therefore (68) t=C [T(U) - T(u)], (69) x = C cos n [S(U) - S(u)1, (70) y =C sin n [S(U) - S(u)], 0-8= C cos n [I (U) - I (u)], (72) tan 0.
    0
    0